Konsep Pengembangan Atraksi Bantimurung berdasarkan Ecotourism - Jureja Jureja; Baharuddin Koddeng; Louis Santoso (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2014)
According to Decision of The Directorate of Forest Protection and Conservation explained in the Long Term Developmetn Planning of Bantimurung Bulusaraung 2008-2027, Bantimurung is a conservation area. Therefore, it needs the ecotourism concept to ensure the sustainability of the ecosystem and the biodiversity. The purpose of this study is to develop Bantimurung attraction based on ecotourism concept. To reach the aim of study, some approaches must be considered, such as observing the physical, economic and social aspects. The physical aspect refers to the ability of ecotourism development to keep the biodiversity and natural environment both during the construction and the operation. The economic aspect refers to the ability of ecotourism development to give the real contribution to improve the local community and government’s economy. The social aspect includes the ability of ecotourism development to provide the attractions that can improve the quality of tourism, management and community. Based on this study, Bantimurung could be developed into ecotourism area because it can reach the criteria of ecotourism concepts like having the magic and beauty of nature (topography), having a diversity of flora fauna, and having a variety of facilities to observe the wildlife. The development concept refers to the concept of zoning district. Every zone must be provided by tourist attractions, facilities and the participation of local communities.